Seni Bicara Lewat Typeface Dekoratif dan Komposisi - Rahardja, Anita; Adiwijaya, Dominique Rio (Humaniora, 2014)
On this essay, the main topic is related to one of the branch in visual communication design, typography. In the early days, typography derives from hand writing, but nowadays, it has been developed digitally by means of computer. The presence of computers facilitate in making digital typefaces, especially decorative ones. This contributes to its quantities and vast distribution. Literature studies conducted to further understand the definitions and characteristics of digital typefaces. A decorative typeface owns a certain visual characteristic which in the end limits its usage. Certain characters in decorative typefaces often associated with particular moods or impressions, which can be used to deliver a message. Next is the ideation and visualization by students and teaching staffs in typography class using both analog and digital media to produce typographic compositions using decorative typefaces. The final step is to analyze the compositions to capture its intended message.